Lexical Hedges in Reflecting Gender Differences - Ayu Amartha Sabhagani; Ni Luh Nyoman Seri Malini; Made Detriasmita Saientisna (Research And Innovation In Language Learning (RILL), 2022)
The study discusses lexical hedges in reflecting gender differences through the movie and analyzes the features of lexical hedges used in Sierra Burgess Is a Loser movie. The data were processed by categorizing the data into components of lexical hedges based on the framework of hedges proposed by Namasaraev (1997) and the sequential positions of lexical hedges proposed by Rosanti&Jaelani (2016). The use of nine types of lexical hedges conforming to its classification by the male and female characters showed a different number of results. As a result, female characters tend to more used lexical hedges rather than men characters. The female characters were mostly used lexical hedges as fillers yeah in their utterance to show their feelings, emotion, or opinion in the movie. The total data showed the number of female characters in using lexical hedges was 92 words sequentially from the most commonly used, i.e. fillers, lexical verbs, modal auxiliary verbs, adverb of frequency, adverb, and noun. Meanwhile, male characters used 40 words of lexical hedges and fillers as the most commonly used hedges through the word; like. In this movie, there were two sequential positions of lexical hedges, namely; the initial and medial position. Besides that, the female characters had a wide range of types in uttering the words that contained lexical hedges, whereas the male characters were not too often in selecting the words of lexical hedges. Penelitian ini membahas mengenai penggambaran lexical hedges dalam perbedaan gender melalu isebuah film, serta untuk menganalisis fitur lexical hedges yang digunakan dalam film Sierra Burgess Is a Loser. Data sudah diproses dengan mengkategorikan data menjadi komponen lexical hedges berdasarkan kerangka hedges yang disusun oleh Namasaraev (1997) dan posisi sekuensial lexical hedges yang diusulkan oleh Rosanti & Jaelani (2016). Penggunaan dari sembilan tipe lexical hedges berdasarkan klasifikasi oleh karakter pria dan wanita menampilkan hasil yang berbeda. Hasilnya, karakter wanita cenderung menggunakan lexical hedges dibandingkan dengan karakter pria. Karakter wanita paling sering menggunakan fitur lexical hedges sebagai fillers yaitu; yeah dalam ucapan mereka untuk menunjukkan perasaan, emosi, dan opini di dalam film. Total data menunjukkan penggunaan lexical hedges oleh karakter wanita berjumlah 92 kata yang secara beruratan dari yang paling sering digunakan yakni fillers, lexical verbs, modal auxiliary verbs, adverb of frequency, adverb, dan noun. Sedangkan, karakter pria menggunakan 40 kata lexical hedges dan fillers like sebagai fitur hedges yang paling sering digunakan. Di dalam film ini, terdapat dua posisi sekuensial dari lexical hedges yakni posisi awal dan posisi tengah. Disamping itu, karakter wanita memiliki jangkauan yang luas mengenai tipe-tipe dalam penyampaian kata yang mengandung fitur lexical hedges, sedangkan karakter pria tidak terlalu sering menggunakan kata lexical hedges didalam pemilihan kata